Production of Gamma-Aminobutyric Acid by Levilactobacillus brevis CD0817 by Coupling Fermentation with Self-Buffered Whole-Cell Catalysis - Haixing Li; Tianyi Sun; Mengya Jia; Lingqin Wang; Cheng Wei; Jinfeng Pei; Zhiyu Lin; Shuixing Wang (Fermentation, 2022)
There is a recent trend of using lactic acid bacteria for the production of gamma-aminobutyric acid (GABA). This study described a method that combines fermentation and self-buffered whole-cell catalysis for the efficient production of GABA using Levilactobacillus brevis CD0817. Upon the completion of GABA fermentation, cells were recovered to conduct whole-cell catalysis by which the substrate L-glutamic acid was catalytically decarboxylated to GABA. L-glutamic acid itself maintained the acidity essential for decarboxylation. To maximize the whole-cell catalysis ability, the effects of the cell culture method, catalysis temperature, catalysis time, cell concentration, and L-glutamic acid dosage were investigated. The results illustrate that the cells that were cultivated for 16 h in a fermentation medium supplemented with 20.0 g/L of glucose were the most suitable for the whole-cell catalytic production of GABA. At 16 h, the fermentative GABA content reached 204.2 g/L. Under optimized whole-cell catalytic conditions (temperature 45.0 °C, time 12.0 h, wet cells 25.0 g/L, and L-glutamic acid 120.0 g/L), 85.1 g/L of GABA was obtained, with 3.7 ± 0.9 g/L of substrate residue. GABA was recovered from the system by sequentially performing rotary vacuum evaporation, precipitation with ethanol, filtration with filter paper, and drying. The purity of the GABA product reached 97.1%, with a recovery rate of 87.0%. These data suggest that the proposed method has potential applications in the production of GABA.